Razširjenost in ekološke značilnosti prsti v dolini reke Rižane - Vovk Korže, Ana (Annales. Series historia naturalis, 1999)
The contribution shows which soils in the area of the river Rižana valley are appropriate for the different type of the usage. Based on the konwledge about the distribution of the type of soils and their ecological properties their type of use is studied and discussed. The following work methods were applied: collecting the data about the types of soils (in the proportion 1:25000) and drawing the map about the spread of type of soils in the proportion 1:50000, setting the figures of merit for the evaluation of ecological properties of the soils and determining the suitable usage ...
Keywords: ekološko ravnotežje; prst; Rižana; sustainable development; trajnostni razvoj